Metal organic nano cross-linked network-based solid electrolyte and preparation method thereof
Through the preparation of solid electrolytes based on metal-organic nanocrosslinking network, the ion conduction capability and stability of electrolytes in solid-state lithium-based batteries are solved, and high-efficiency lithium ion conduction and cell cycle stability are achieved. It is suitable for lithium metal and lithium Air battery.
Patent Information
- Application Number
- CN202411397557.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The solid electrolytes of existing solid lithium-based batteries have shortcomings in ionic conductivity, processability and stability, which limits their application, especially the difficulty of preparing inorganic solid electrolytes and the problem of lithium dendrites, and the room temperature ions of polymer solid electrolytes. Low conductivity and poor electrochemical stability.
Using the preparation method of metal-organic nanocrosslinking network-based solid electrolyte, by using butyraldehyde, phragtopol, magnesium nitrate hexahydrate, polyethylene glycol, polyethylene oxide and lithium bistrifluoromethanesulfonamide The acetonitrile is dissolved and cast into a film by sonication to form a PolyMONC (Li) electrolyte with continuous ion transport paths and metal organic nanocapsule structure, limiting anions and promoting rapid conduction of lithium ions.
It achieves high lithium ion conductivity and migration number, inhibits the growth of lithium dendrites, improves the specific capacity of lithium metal batteries and the cycling stability of lithium air batteries, reduces the interface resistance, and improves the overall performance of the battery.
Smart Images

Figure CN119253050A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a metal organic nano cross-linked network-based solid electrolyte and a preparation method thereof. Background Art
[0002] As the mainstream energy storage device, the energy density of lithium-ion batteries is close to the theoretical limit, but it is still difficult to meet the growing demand. The energy density of lithium metal batteries obtained by replacing the graphene negative electrode with lithium metal can be greatly improved. In addition, lithium-air batteries have a high energy density of up to 3500 Wh kg -1 The theoretical energy density of non-aqueous lithium batteries has attracted widespread attention. However, the organic electrolytes commonly used in non-aqueous lithium batteries are flammable and volatile, and the batteries have the potential safety hazard of explosion. At the same time, the growth of lithium dendrites will cause the battery volume to expand, seriously damaging the battery structure and causing battery failure. Using solid electrolytes instead of organic electrolytes to manufacture stable and safe solid-state lithium-based batteries is an effective strategy to solve the existing thorny problems of lithium-based batteries.
[0003] Existing solid electrolytes are mainly divided into inorganic solid electrolytes and polymer solid electrolytes. Inorganic solid electrolytes have the advantages of high room temperature ionic conductivity, good electrochemical stability, high flame retardancy, high mechanical strength, etc., and have broad application prospects; polymer solid electrolytes have high flexibility, excellent processability and good interface compatibility.
[0004] Although solid-state lithium-based batteries have good prospects, they are still in their infancy and many scientific and technological problems remain to be solved. An ideal solid electrolyte should have high ionic conductivity, excellent processability and good stability. However, the difficulty of large-scale preparation of inorganic solid electrolytes, large interfacial resistance and growth of lithium dendrites along grain boundaries have greatly limited their practical applications. The problems faced by polymer solid electrolytes, such as low room temperature ionic conductivity, poor electrochemical stability and low mechanical strength, also limit their development. At present, the traditional solid electrolytes used in solid-state lithium-based batteries are not sufficient to simultaneously achieve the requirements of high ionic conductivity, easy processing and high stability. Therefore, the development of safe and high-performance solid electrolytes is of great significance for the construction of solid-state lithium-based batteries with excellent performance and high safety. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a method for preparing a metal-organic nano-cross-linked network-based solid electrolyte, aiming to solve the problems raised in the above-mentioned background technology.
[0006] The embodiment of the present invention is implemented as follows: a method for preparing a metal organic nano cross-linked network-based solid electrolyte, characterized in that it comprises the following steps: (1) Mix butyraldehyde and pyrogallol in ethanol, stir evenly, drop concentrated hydrochloric acid into the mixture while stirring, and then stir and reflux the mixture; (2) cooling the reactant of step (1), filtering under reduced pressure, repeatedly washing with ethanol, and vacuum drying to obtain C-propylpyrogallol[4]arene; (3) dissolving C-propylpyrogallol[4]arene, magnesium nitrate hexahydrate, polyethylene glycol, polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide in acetonitrile, and adding pyridine after dissolution; (4) ultrasonically treating the solution in step (3) and then stirring to obtain a PolyMONC (Li) solution; (5) The PolyMONC (Li) solution is poured onto a polytetrafluoroethylene mold, and the solid electrolyte material is obtained after the solvent is completely evaporated.
[0007] Another object of an embodiment of the present invention is to provide a polymer metal organic nano cross-linked network-based solid electrolyte material prepared by the above preparation method.
[0008] Preferably, the polymer metal organic nano cross-linked network-based solid electrolyte material is a peelable film-like material.
[0009] The solid electrolyte prepared by PolyMONC (Li) provided in the embodiment of the present invention has a high lithium ion conductivity due to its continuous ion transmission path, and realizes the rapid conduction of lithium ions. At the same time, the unique cage structure, pore size and a large number of metal open sites on the structural skeleton of the metal organic nanocapsule can confine the lithium salt anions in the molecular cage. The fixation of the anions weakens the Coulomb effect of anions and cations in the electrolyte, thereby obtaining a higher lithium ion migration number. At the same time, the fixation of the anions is conducive to the uniform deposition of lithium ions, avoiding the generation of local large electric fields, effectively inhibiting the growth of lithium dendrites, and providing a guarantee for the stable operation of the subsequent battery. The solid electrolyte material of the embodiment of the present invention can be applied to lithium metal batteries. Thanks to the high ionic conductivity and high ion transfer number of PolyMONC (Li), lithium metal batteries have a higher specific capacity. The polymer metal organic nano cross-linked network-based solid electrolyte-air positive electrode integrated material of the embodiment of the present invention solves the problems of large interface resistance between the solid electrolyte and the solid positive electrode and slow ion transmission in traditional solid-state batteries. It provides a close interface contact, effectively reduces the ion transmission resistance between the interfaces, and realizes efficient and stable transmission of lithium ions. At the same time, the constructed three-phase interface realizes the function of rapid conduction of lithium ions, electrons and oxygen, which is conducive to the construction of efficient and stable lithium-air batteries. The polymer metal organic nano cross-linked network based solid electrolyte-air positive electrode integrated material of the embodiment of the present invention can be applied to lithium-air batteries, wherein the positive electrode adopts the polymer metal organic nano cross-linked network based solid electrolyte-air positive electrode integrated material, which greatly reduces the interface impedance, and the rate performance and cycle stability of the lithium-air battery are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a SEM image of the PolyMONC (Li) electrolyte membrane provided in Example 1 of the present invention; Figure 2 This is a graph showing the ionic conductivity results of the PolyMONC (Li) electrolyte membrane provided in Example 1 of the present invention; Figure 3 This is a graph showing the ion migration number results of the PolyMONC (Li) electrolyte membrane provided in Example 1 of the present invention; Figure 4 The specific capacity performance results of the PolyMONC (Li) solid-state lithium metal battery provided in Example 2 of the present invention; Figure 5 A cross-sectional SEM image of the polymer metal organic nano cross-linked network-based solid electrolyte-air cathode integrated material provided in Example 3 of the present invention; Figure 6 The cycle stability results of the PolyMONC (Li) solid-state lithium-air battery provided in Example 4 of the present invention; Figure 7 The cycle stability results of the polyethylene oxide (PEO(Li)) lithium-air battery provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0012] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0013] Embodiment 1: A PolyMONC (Li) electrolyte membrane, the preparation method of which comprises the following steps: (1) First, take 7.21 mL of butyraldehyde and 10 g of pyrogallol in a 100 mL beaker, add 40 mL of 95% ethanol, stir evenly until the solid is completely dissolved, drop 3.5 mL of concentrated hydrochloric acid, stir while adding, then transfer the mixture to a 100 mL round-bottom flask, stir and reflux at 110 °C for 24 h, and obtain a reddish-brown solution after the reaction. Cool to room temperature, filter the obtained solution under reduced pressure, and repeatedly wash with 95% ethanol to obtain white solid C-propylpyrogallol[4]arene (PgC3), which is vacuum dried at 80 °C for 24 h with a yield of 37.5%; (2) Weigh 0.48 g PgC3, 0.68 g magnesium nitrate hexahydrate, 0.08 g polyethylene glycol (molecular weight 1500), and 0.72 g polyethylene oxide (molecular weight 600000), grind them evenly, transfer the mixture to a glove box, add 1.38 g lithium bis(trifluoromethanesulfonyl)imide to the glove box, mix evenly, add 25 mL anhydrous acetonitrile, add 100 μL pyridine after stirring evenly, sonicate for 5 min until the solution is uniform and free of lumps, then transfer the solution to a 50 mL round-bottom flask, reflux and stir at 110 °C for 12 hours until the solution changes from yellow to black, and obtain PolyMONC(Li) solution (the reactants must be in an anhydrous and oxygen-free environment); (3) The reacted PolyMONC (Li) solution was cast on a polytetrafluoroethylene mold. After the solution evaporated completely, the polytetrafluoroethylene mold was transferred to a glove box and further dried for 3 days to obtain a PolyMONC (Li) electrolyte membrane. The obtained electrolyte could be completely peeled off as an independent membrane.
[0014] Performance Test: The product prepared in Example 1 was characterized by scanning electron microscopy, and the results were as follows: Figure 1 As shown; The conductivity performance of the product prepared in Example 1 was tested. The PolyMONC (Li) electrolyte membrane was cut into electrolyte membrane samples with a diameter of 16 mm using a punching machine. The electrolyte membrane samples were sandwiched between two stainless steel sheets for ion conductivity testing. The measured ion conductivity was 0.18 mS cm −1 ,like Figure 2 As shown; The product prepared in Example 1 was assembled into a lithium metal symmetric battery and the ion migration number was tested to obtain a lithium ion migration number of 0.83. Figure 3 shown.
[0015] Example 2, PolyMONC (Li) solid-state lithium metal battery, the preparation method thereof comprises the following steps: in a glove box, the negative electrode lithium sheet, the PolyMONC (Li) electrolyte membrane prepared in Example 1, and commercial LiFePO4 are placed on a 2032 negative electrode shell in sequence, and finally the 2032 positive electrode shell is covered and assembled, the battery is placed on a battery packaging machine, and the battery is placed on a 50 kg cm −2 The solid-state lithium metal battery is packaged under pressure of 2032.
[0016] Performance Test: The solid-state lithium metal battery prepared in Example 2 was tested. The discharge capacity of the lithium metal battery was as high as 151.1 mAh g at a current density of 0.06 C. −1 ,like Figure 4 shown.
[0017] Example 3, polymer metal organic nano cross-linked network based solid electrolyte-air positive electrode integrated material, the preparation method thereof comprises the following steps: weighing 0.1 g of carbon nanotubes into a glass bottle, adding 25 mL of the PolyMONC (Li) solution in Example 1, stirring at room temperature for 24 h, casting the mixed slurry on the electrolyte membrane prepared in Example 1, drying at 60°C for 3 days, and obtaining an integrated functional positive electrode after the solvent is completely evaporated.
[0018] Performance Test: The integrated functional positive electrode prepared in Example 3 was cut and the scanning electron microscope image of its cross section was tested, and the results were as follows: Figure 5 shown.
[0019] Example 4, PolyMONC (Li) solid-state lithium-air battery, the preparation method thereof comprises the following steps: in a glove box, placing the negative electrode lithium sheet, the integrated functional positive electrode prepared in Example 3 and the positive electrode current collector on a 2025 negative electrode shell in sequence, and finally assembling the 2025 positive electrode shell with holes, placing the battery on a battery packaging machine, and heating the battery at 50 kg cm −2 The solid-state lithium-air battery is packaged under pressure of 2025.
[0020] Performance Test: The PolyMONC (Li) solid-state lithium-air battery prepared in Example 4 was tested at 10 mA g −1 It can cycle 500 times at a current density of Figure 6 As shown, it is proved that the solid-state lithium-air battery has good electrochemical performance.
[0021] Comparative Example 1: A polyethylene oxide (PEO(Li)) lithium-air battery, the preparation method of which comprises the following steps: (1) Weigh 1.44 g polyethylene oxide and 0.16 g polyethylene glycol, grind them evenly in a mortar and transfer them to a glove box. Weigh 1.74 g lithium bis(trifluoromethanesulfonyl)imide and add them to the above mixture. Add 50 mL acetonitrile and stir at room temperature for 24 h. Pour the uniform PEO(Li) slurry into a polytetrafluoroethylene mold and dry it at 60 °C for 3 days. After the solvent is completely evaporated, a strippable PEO(Li) electrolyte membrane is obtained. (2) Weigh 0.2 g of carbon nanotubes into a glass bottle, add 50 mL of PEO(Li) solution, stir at room temperature for 24 h, cast the mixed slurry on the electrolyte membrane, dry at 60 °C for 3 days, and obtain an integrated functional positive electrode after the solvent is completely evaporated; (3) In a glove box, the negative electrode lithium sheet, the integrated functional positive electrode of step (2) and the positive electrode current collector are placed on the negative electrode shell in sequence, and finally the positive electrode shell with holes is covered and assembled, and the battery is placed on a battery packaging machine. After packaging, a solid-state lithium-air battery is obtained, and the battery specification is 2025.
[0022] Performance Test: The polyethylene oxide (PEO(Li)) lithium-air battery prepared in Comparative Example 1 was tested at 10 mA g −1 The current density is cycled for 136 times. Figure 7 As shown, it can be seen that its cycle performance is poor compared with the PolyMONC (Li) lithium-air battery prepared in Example 4 of the present invention.
[0023] In summary, the PolyMONC (Li) solid electrolyte prepared in the embodiment of the present invention can realize efficient transmission of lithium ions by utilizing its continuous ion transmission path. At the same time, the metal organic nanocapsules in the polymer-based metal organic nano cross-linked network have a unique cage structure and a large number of metal open sites. On the one hand, they can effectively fix anions on the skeleton structure to achieve a higher lithium ion migration number; on the other hand, the anchoring of anions is conducive to the rapid and uniform deposition of lithium ions, which can effectively avoid the generation of a large electric field caused by excessive local current density, effectively inhibit the growth of lithium dendrites, and solve the problems of poor ion conductivity and poor chemical / electrochemical stability of existing solid electrolytes; the PolyMONC (Li)-based solid-state lithium metal battery prepared in the embodiment of the present invention has a higher specific capacity due to the high ionic conductivity and high ion migration number of PolyMONC (Li); the solid electrolyte-air positive electrode integrated material prepared in the embodiment of the present invention effectively solves the problem of poor solid-solid interface contact between the solid electrolyte and the solid positive electrode in traditional solid-state batteries, and constructs a rich three-phase interface; the solid-state lithium-air battery prepared in the embodiment of the present invention exhibits excellent cycle stability and has good application prospects.
[0024] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal organic nano cross-linked network-based solid electrolyte, characterized in that: The following steps are involved: (1) Mix butyraldehyde and pyrogallol in ethanol, stir evenly, drop concentrated hydrochloric acid into the mixture while stirring, and then stir and reflux the mixture; (2) cooling the reactant of step (1), filtering under reduced pressure, repeatedly washing with ethanol, and vacuum drying to obtain C-propylpyrogallol[4]arene; (3) dissolving C-propylpyrogallol[4]arene, magnesium nitrate hexahydrate, polyethylene glycol, polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide in acetonitrile, and adding pyridine after dissolution; (4) ultrasonically treating the solution in step (3) and then stirring to obtain a PolyMONC (Li) solution; (5) The PolyMONC (Li) solution is poured onto a polytetrafluoroethylene mold, and the solid electrolyte is obtained after the solvent is completely evaporated.
2. A metal-organic nano-cross-linked network-based solid electrolyte prepared by the preparation method as claimed in claim 1.
3. The metal organic nano cross-linked network based solid electrolyte according to claim 2, characterized in that: The solid electrolyte is a peelable film material.
Citation Information
Patent Citations
Cross-linked organic-inorganic nano material modified solid polymer electrolyte and preparation method thereof
CN115911543A
Cationic super-crosslinking metal-organic cage composite membrane, solid electrolyte, lithium metal battery and preparation method and application thereof
CN118712460A